Negotiating Wasatiyyah: Soft Securitization and Civic Activism in Ukraine - Yarosh, Oleg (Religions, 2025)
This article addresses religious governance in Ukraine in relation to local Muslim organizations associated with the Council of European Muslims (CEM), formerly known as the Federation of Islamic Organizations in Europe (FIOE). Specifically, it focuses on the Council of Ukrainian Muslims (CUM), formerly known as Alraid, and the Spiritual Administrations of Ukrainian Muslims Ummah (SAUM Ummah). Addressing the policymaking aspect of securitization, the article concerns state policies in Ukraine as ‘soft securitization’, meaning the execution of limited interventions and restrictions on the activities of Muslim organizations in Ukraine, particularly those at the focus of this article and labeled as ‘Islamist’. The FIOE in Europe and Alraid in Ukraine developed a response to these policies, informed by the wasatiyyah (moderation) post-Islamist ideology. The article analyzes how the wasatiyyah ideology was appropriated and negotiated in the discourse of these Ukrainian organizations, and how it informed their civic activism.